Importance of Exercise Capacity in Predicting Outcomes and Determining Optimal Timing of Surgery in Significant Primary Mitral Regurgitation. Issue 5 (11th September 2014) - Naji, Peyman; Griffin, Brian P.; Barr, Tyler; Asfahan, Fadi; Gillinov, A. Marc; Grimm, Richard A.; Rodriguez, L. Leonardo; Mihaljevic, Tomislav; Stewart, William J.; Desai, Milind Y.
Abstract : Background: In primary mitral regurgitation (MR), exercise echocardiography aids in symptom evaluation and timing of mitral valve (MV) surgery. In patients with grade ≥3 primary MR undergoing exercise echocardiography followed by MV surgery, we sought to assess predictors of outcomes and whether delaying MV surgery adversely affects outcomes. Methods and Results: We studied 576 consecutive such patients (aged 57±13 years, 70% men, excluding prior valve surgery and functional MR). Clinical, echocardiographic (MR, LVEF, indexed LV dimensions, RV systolic pressure) and exercise data (metabolic equivalents) were recorded. Composite events of death, MI, stroke, and congestive heart failure were recorded. Mean LVEF was 58±5%, indexed LV end‐systolic dimension was 1.7±0.5 mm/m 2, rest RV systolic pressure was 32±13 mm Hg, peak‐stress RV systolic pressure was 47±17 mm Hg, and percentage of age‐ and gender‐predicted metabolic equivalents was 113±27. Median time between exercise and MV surgery was 3 months (MV surgery delayed ≥1 year in 28%). At 6.6±4 years, there were 53 events (no deaths at 30 days). On stepwise multivariable survival analysis, increasing age (hazard ratio of 1.07 [95% confidence interval, 1.03 to 1.12], P <0.01), lower percentage of age‐ and gender‐predicted metabolic equivalents (hazard ratio of 0.82 [95% confidence interval, 0.71 to 0.94], P =0.007), and lower LVEF (0.94 [0.89 to 0.99], P =0.04) independently predicted outcomes. In patients achieving >100% predicted metabolic equivalents (n=399), delaying surgery by ≥1 year (median of 28 months) did not adversely affect outcomes ( P =0.8). Conclusion: In patients with primary MR that underwent exercise echocardiography followed by MV surgery, lower achieved metabolic equivalents were associated with worse long‐term outcomes. In those with preserved exercise capacity, delaying MV surgery by ≥1 year did not adversely affect outcomes.